Influenza Vaccination to Reduce Cardiovascular Morbidity and Mortality in Patients With COVID-19: JACC State-of-the-Art Review - Behrouzi, Bahar (J Am Coll Cardiol, 2020)
Viral respiratory infections are risk factors for cardiovascular disease (CVD). Underlying CVD is also associated with an increased risk of complications following viral respiratory infections, including increased morbidity, mortality, and health care utilization. Globally, these phenomena are observed with seasonal influenza and with the current coronavirus disease 2019 (COVID-19) pandemic. Persons with CVD represent an important target population for respiratory virus vaccines, with capacity developed within 3 large ongoing influenza vaccine cardiovascular outcomes trials to determine the potential cardioprotective effects of influenza vaccines. In the context of COVID-19, these international trial networks may be uniquely positioned to redeploy infrastructure to study therapies for primary and secondary prevention of COVID-19. Here, we describe mechanistic links between influenza and COVID-19 infection and the risk of acute cardiovascular events, summarize the data to date on the potential cardioprotective effects of influenza vaccines, and describe the ongoing influenza vaccine cardiovascular outcomes trials, highlighting important lessons learned that are applicable to COVID-19.